A Framework for Quality Control, Accountability, and Evaluation: Being Clear About the Legitimate Outcomes of Career Counselling - Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 2007)
The main argument in this paper is that as career and employment counselling drift away from their educational roots towards a psychological focus emphasizing standardized assessment and process to the exclusion of outcome, accountability issues become harder to address. A new model for evaluation is necessary: one that counsellors see as relevant and practical, that can address both formative and summative evaluation concerns, and is capable of embracing the informal observations that counsellors and clients make about counselling progress. An alternative model is described in this paper and sample evaluation instruments are provided.